Cytotoxicity and physicochemical characterization of iron–manganese-doped sulfated zirconia nanoparticles - Al-Fahdawi, Mohamed Qasim; Abdullah, Rasedee; Al-Qubaisi, Mothanna Sadiq; Alhassan, Fatah H.; Rosli, Rozita; El Zowalaty, Mohamed Ezzat; Naadja, Seïf-Eddine; Webster, Thomas J.; Taufiq-Yap, Yun Hin (Dove Medical Press, 2015)
Iron–manganese-doped sulfated zirconia nanoparticles with both Lewis and Brønsted acidic sites were prepared by a hydrothermal impregnation method followed by calcination at 650°C for 5 hours, and their cytotoxicity properties against cancer cell lines were determined. The characterization was carried out using X-ray diffraction, thermogravimetric analysis, Fourier transform infrared spectroscopy, Brauner–Emmett–Teller (BET) surface area measurements, X-ray fluorescence, X-ray photoelectron spectroscopy, zeta size potential, and transmission electron microscopy (TEM). The cytotoxicity of iron–manganese-doped sulfated zirconia nanoparticles was determined using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assays against three human cancer cell lines (breast cancer MDA-MB231 cells, colon carcinoma HT29 cells, and hepatocellular carcinoma HepG2 cells) and two normal human cell lines (normal hepatocyte Chang cells and normal human umbilical vein endothelial cells [HUVECs]). The results suggest for the first time that iron–manganese-doped sulfated zirconia nanoparticles are cytotoxic to MDA-MB231 and HepG2 cancer cells but have less toxicity to HT29 and normal cells at concentrations from 7.8 µg/mL to 500 µg/mL. The morphology of the treated cells was also studied, and the results supported those from the cytotoxicity study in that the nanoparticle-treated HepG2 and MDA-MB231 cells had more dramatic changes in cell morphology than the HT29 cells. In this manner, this study provides the first evidence that iron–manganese-doped sulfated zirconia nanoparticles should be further studied for a wide range of cancer applications without detrimental effects on healthy cell functions.